Skeleton crew - King, Stephen, 1947- (1985)
Age-old images of fear fuse with the iconography of contemporary American life in this collection of tales from the modern master of horror
The mist -- Here there be tygers -- The monkey -- Cain rose up -- Mrs. Todd's shortcut -- The jaunt -- The wedding gig -- Paranoid: a chant -- The raft -- Word processor of the gods -- The man who would not shake hands -- Beachworld -- The reaper's image -- Nona -- For Owen -- Survivor type -- Uncle Otto's truck -- Morning deliveries (Milkman #1) -- Big wheels: a tale of the laundry game (Milkman #2) -- Gramma -- The ballad of the flexible bullet -- The reach
Keywords: Horror tales, American; Horror tales